Rancang Bangun Overhead Crane Automatic Berbasis Arduino - Panji Bintang Pratama; Intan Sianturi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Overhead cranes are an important device in the manufacturing and construction industry that functions to move heavy loads efficiently and safely. However, human error often occurs which can cause work accidents, equipment damage, and decreased productivity. Therefore, this research aims to design and build an Arduino-based automatic overhead crane system that can increase work efficiency and safety. This system is designed using an Arduino microcontroller as a control center, equipped with an ultrasonic sensor to detect the position and distance of the load, as well as a servo motor to regulate crane movement automatically. The system also features a wireless communication module to monitor and control the crane remotely. The research method used is Research and Development (R&D), which includes the stages of needs analysis, system design, hardware and software implementation, and performance testing. Test results show that this automatic overhead crane is capable of moving loads with high accuracy and a speed that can be adjusted according to needs. The system also succeeded in reducing manual intervention, thereby increasing work safety and reducing the risk of accidents by up to 30% compared to manual systems. The Arduino-based automatic overhead crane design succeeded in meeting the research objectives, increasing work efficiency and safety. Routine maintenance and periodic checks on mechanical and electronic components need to be carried out to ensure the system continues to function optimally and reduces the risk of damage.